Upaya Petani Jamur Tiram Putih sebagai Alternatif Usaha dalam Meningkatkan Perekonomian Masyarakat Kecamatan Sako Kota Palembang - Titania Fetricia (Fakultas Dakwah IAIN Jember, 2023)
White oyster mushroom (Pleuratus Florida) is one of the types of mushrooms that has become an alternative due to its beneficial nutritional content for the body, making it a promising business opportunity and an alternative for the community. However, to achieve success in oyster mushroom cultivation and business, the right knowledge and the courage to try are needed. The objectives of this study are to: 1) understand the history of oyster mushroom cultivation, 2) understand community responses to oyster mushroom cultivation, and 3) identify factors inhibiting oyster mushroom cultivation. This study uses qualitative research, with the author acting as an observer, directly observing the phenomena and behaviors to be studied. The results of this study indicate that: 1) Oyster mushroom cultivation has been done in China for 1,000 years and is popular in Indonesia as an alternative source of income for communities, and is not too complicated; 2) White oyster mushroom cultivation can be an alternative business for communities facing economic crises. This business is suitable for urban communities, with high demand, low capital, and easy to do; 3) Inhibiting factors in oyster mushroom cultivation lie in the farmer's expertise and factors such as temperature, light, air, pH, and humidity should be considered. Oyster mushroom cultivation can help improve the community's economy and open up business opportunities.